Visual strategies of young soccer players during a passing test - A pilot study - Pieter Vansteenkiste; Matthieu Lenoir; Izabela Krejtz; Krzysztof Krejtz (Bern Open Publishing, 2022)
In sports, studies on visual behavior have mostly focused on expert-novice differences during decision making tasks and during aiming tasks. How visual behavior changes during the early stages of skill acquisition however, has hardly been documented. The current study investigated gaze behavior of young soccer players during the execution of a soccer passing task. Gaze behavior of eleven 8- to 10-year-old soccer players was recorded while they performed the Loughborough Soccer Passing Test. Based on their score, participants were then divided into a high performance group (N=5), and a low performance group (N=6). Results showed that the low performance group tended to look more at the ball while they were handling it. These findings suggest that gaze strategies develop alongside technical skills. More insights in the interplay between technical skills and gaze strategies during skill acquisition could lead to improved training methods for young soccer players.